2016
DOI: 10.1371/journal.pone.0160848
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD14 Enhances the Response of Periodontal Ligament Stem Cells to P. gingivalis Lipopolysaccharide

Abstract: Periodontal ligament stem cells (PDLSCs) are lacking membrane CD14, which is an important component of lipopolysaccharide (LPS) signaling through toll-like receptor (TLR) 4. In the present study we investigated the effect of soluble CD14 on the response of human PDLSCs to LPS of Porphyromonas (P.) gingivalis. Human PDLSCs (hPDLSCs) were stimulated with P. gingivalis LPS in the presence or in the absence of soluble CD14 (sCD14) and the production of interleukin (IL)-6, chemokine C-X-C motif ligand 8 (CXCL8), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 52 publications
4
57
3
1
Order By: Relevance
“…Interestingly, our previous studies show that the response of hPDLSCs to TLR‐4 agonist E. coli LPS is substantially (up to 10‐fold) lower compared with that of Pam3CSK4, although TLR‐4 receptors uses both MyD88‐dependent and MyD88‐independent signaling . This observation is quite surprising, because in the present study we showed that simultaneous activation of MyD88‐dependent and MyD88‐independent pathway leads to synergistic effects on IL‐6, IL‐8, and MCP‐1 production.…”
Section: Discussioncontrasting
confidence: 40%
“…Interestingly, our previous studies show that the response of hPDLSCs to TLR‐4 agonist E. coli LPS is substantially (up to 10‐fold) lower compared with that of Pam3CSK4, although TLR‐4 receptors uses both MyD88‐dependent and MyD88‐independent signaling . This observation is quite surprising, because in the present study we showed that simultaneous activation of MyD88‐dependent and MyD88‐independent pathway leads to synergistic effects on IL‐6, IL‐8, and MCP‐1 production.…”
Section: Discussioncontrasting
confidence: 40%
“…For this reason, the response to TLR2/1 agonist Pam3CSK4 and TLR4 agonist E. coli LPS was compared between pretreated and non‐pretreated cells. Additionally, both P. gingivalis LPS and E. coli LPS were administered together with sCD14 in a physiologically relevant concentration …”
Section: Discussionmentioning
confidence: 99%
“…The expression of TLR2 and TLR4 is altered in periodontal disease and therefore these receptors are discussed to play an important role in disease progression . TLR4 activation by different bacterial LPS induces the production of inflammatory mediators in hPDLCs . Similarly, TLR2 activation results in cytokine production by PDLs and gingival fibroblasts …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations